THE IMPLEMENTATION OF STANDARD APPROACH FOR OPEN SPACE PLANNING IN KUALA LUMPUR - Suratman, Robiah; Mohd Raid, Maryanti; Nadzri, Muhammad Izuan; Samsudin, Salfarina; Mohammad, Nur Khairiyah (PLANNING MALAYSIA, 2020)
This article attempts to discuss the implementation of standards approach, 2 hectares per 1000 population as approved by the National Physical Planning Council in 2005. Using Kuala Lumpur as case study, the analysis showed that the uniformity of standards approach implementation has failed to take into account the distinction within the local conditions which have implications on the level of achievement for the 6 planning zones in Kuala Lumpur from 2011 to 2017. Use of the standards approach without modifications has created high density zones such as the City Centre, Sentul-Manjalara and Wangsa Maju-Maluri failed to attain the standards. Besides, other zones namely Damansara-Penchala, Bandar Tun Razak-Sungai Besi and Bukit Jalil-Seputih have exceeded the targeted standards. Based on the analysis, the distinction of local condition for each zone in Kuala Lumpur in terms of population number, urban land availability, land value, urbanization process and densification rate of the city need to be considered in implementing standards approach.